Soul snatchers : the mechanics of cults - Abgrall, Jean-Marie (Algora Pub., 2000)
March 1997: One year after the massacre of Saint-Pierre-of-Charennes and the death of 16 cult members of the Order of the Solar Temple, in Saint-Casimir, Canada, five other members of the order rejoin their brothers in death. In San Jose, California, 39 members of the Gates of Paradise follow their guru in death to reach the Hale Bopp Comet that was to take them to a faraway planet. Not all cults manifest in such a dramatic way, but many achieve their goals subtly and incrementally. As with drug addiction, the phenomenon of cults hits all social strata and plants its roots in the deepest core of the individual. Mental manipulation uses the most up-to-date techniques of communication, marketing and persuasion, and requires a complex organization. Jean-Marie Abgrall, psychiatrist, criminologist, expert witness to the French Court of Appeals, and member of the Inter-Ministry Committee on Cults, is one of the experts most frequently consulted by the European judicial and legislative processes. The fruit of 15 years of research, his book delivers the first methodical analysis of the sectarian phenomenon, decoding the mental manipulation on behalf of mystified observers as well as victims. To describe this psychopathology and the means to resist it, the author applies the framework of criminology and medico-legal psychiatry. He feels that cults, whose brainwashing essentially equates to enslavement, should be subject to criminal law. "Some cults resort to severe methods to subjugate and re-indoctrinate rebellious initiates (sleep deprivation, starvation, daily public confessions), some use sexual entrapment or drugs, [but] most cults ... use subtle techniques." Jean-Marie Abgrall details the mechanisms by which cults attract, ensnare and brainwash new members. The book discusses types of people most vulnerable to cult recruitment; in fact, it gives you everything you'd need to know, if you want to start a cult of your own! Not all cults manifest so dramatically; many weave their spells quietly and patiently. Like drug addiction, the cult phenomenon hits all social strata and plants its roots in the deepest core of the individual. Cults use state-of-the art techniques to manipulate their followers, and develop complex organizations to expand and grow. Cult members are led to dissolve their individual selves into the group, to become emotionally dependent on the guru, to espouse a certain doctrine and gradually to cut themselves off from normal life